THE INFLUENCE OF WORK ENVIRONMENT AND WORK DISCIPLINE ON WORK PERFORMANCE WITH JOB PROMOTION AS AN INTERVENING VARIABLE EMPLOYEES OF PT PLN (PERSERO) UP3 PEMATANGSIANTAR - Harnita Siringoringo (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of the work environment and work discipline on employee performance, with job promotion as an intervening variable at PT PLN (Persero) UP3 Pematangsiantar. This quantitative study used the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method with SmartPLS 3.3.3 software. Data were collected through questionnaires from 72 permanent employees. The results are expected to provide insight into the importance of the work environment and work discipline in improving employee performance and the role of job promotion as a mediating factor.